Dosimetric accuracy of Acuros® XB and AAA algorithms for stereotactic body radiotherapy (SBRT) lung treatments: evaluation with PRIMO Monte Carlo code - Sarin, B.; Bindhu, B.; Raghu Kumar, P.; Sumeesh, S.; Saju, B. (Journal of radiotherapy in practice, 2023)
Purpose:The study aimed to compare the dosimetric performance of Acuros® XB (AXB) and anisotropic analytical algorithm (AAA) for lung SBRT plans using Monte Carlo (MC) simulations.Methods:We compared the dose calculation algorithms AAA and either of the dose reporting modes of AXB (dose to medium (AXB-Dm) or dose to water (AXB-Dw)) algorithms implemented in Eclipse® (Varian Medical Systems, Palo Alto, CA) Treatment planning system (TPS) with MC. PRIMO code was used for the MC simulations. The TPS-calculated dose profiles obtained with a multi-slab heterogeneity phantom were compared to MC. A lung phantom with a tumour was used to validate TPS algorithms using different beam delivery techniques. 2D gamma values obtained from Gafchromic film measurements in the tumour isocentre plane were compared with TPS algorithms and MC. Ten VMAT SBRT plans generated in TPS with each algorithm were recalculated with a PRIMO MC system for identical beam parameters for the clinical plan validation. A dose–volume histogram (DVH) based plan comparison and a 3D global gamma analysis were performed.Results:AXB demonstrated better agreement with MC and film measurements in the lung phantom validation, with good agreement in PDD, profiles and gamma analysis. AAA showed an overestimated PDD, a significant difference in dose profiles and a lower gamma pass rate near the field borders. With AAA, there was a dose overestimation at the periphery of the tumour. For clinical plan validation, AXB demonstrated higher agreement with MC than AAA.Conclusions:AXB provided better agreement with MC than AAA in the phantom and clinical plan evaluations.